Educators Thinking Tool (Case Study of Educators' Mindset Against Logic, Language and Mathematics at Keatif Media State Polytechnic) - Gunawan Gunawan; Muhammad Adyan Simanjuntak; Muhammad Zein Damanik; Hasan Bakti Nasution (UMSU, 2022)
The purpose of this research is to systematically find out the process of thinking patterns of educators/lecturers in the classroom, and to find out its effect on the growth of students' academic characters who are logical, use good language and patterns of mathematical systems. The method used is a qualitative method with a descriptive approach, namely describing data analysis of the teaching and learning system of an educator in the classroom and outside the classroom using guided questionnaires and conducting qualitative analysis in order to get good analysis results. The data can show that every educator in the classroom uses elements of logic, language and mathematical development which are very useful in understanding the competence of skills at the Diploma 3 education level of the Politeknik Negeri Media Kreatif which demands an understanding of skill competence. The use of logical, linguistic and mathematical thinking in the classroom by educators/lecturers is a systemic thinking pattern needed in the industrial world.